Direct and indirect effects of zooplanktivorous predators on the estuarine plankton community - Wasserman, Ryan John (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2014)
Although predation has been identified as a potentially important driver in terrestrial and freshwater ecosystems, estuarine planktonic research has focused largely on the so-called "bottom-up" drivers of community assemblages. As such, this thesis focuses on the direct and indirect effects of zooplanktivorous predators on the planktonic community in an estuarine environment. By using a suite of in situ mesocosm experiments, a number of hypotheses, pertaining to the major research themes associated with predator-prey interactions, are tested. These themes included trophic cascading, risk effects associated with predation events and the importance of predator diversity in maintaining prey communities. The first experiment assessed the significance of apex predation pressure for the planktonic community through trophic cascades. Various treatments using in situ mesocosms were established in a closed oligotrophic estuary to highlight the importance of predation in stabilising estuarine plankton abundances. Through either the removal (filtration) or addition of certain planktonic groups, varied trophic scenarios were established. The experimental treatment containing apex zooplanktivores had consequences for multiple trophic levels, exerting a stabilising pressure throughout the food web (Chapter 3). Furthermore, pyrosequencing of filtered water samples revealed that when compared to the remaining treatments, the treatment containing stable apex predatory pressure experienced limited temporal deviation-from-initial in bacterial community structure (Chapter 4). These findings are consistent with trophic cascade theory whereby predators mediate interactions at multiple lower trophic levels with consequent repercussions for diversity. To assess the non-consumptive effects of predators on prey, two experiments were conducted. Firstly, using egg numbers per clutch as a measure of potential reproductive output, the non-lethal effects of predatory pressure on reproductive success in a key planktonic copepod was investigated. In this study, the average clutch size of fecund female copepods was found to be consistently lower in the presence of predators when compared to females not exposed to predation threat (Chapter 5). The second study assessed the effects of conspecific chemical alarm cues associated with predation, on population dynamics of a copepod species. This study revealed that the copepods appear to detect the presence of chemical alarm cues associated with predation events, with repercussions for population demographics over time. Furthermore, it showed that in the absence of actual predation, copepod prey responses to alarm cues were adjusted over time, consistent with the threat sensitive predator avoidance hypo
Keywords: Zooplankton -- Effect of predation on; Predation (Biology); Zooplankton -- Predators of; Copepoda